(untitled) (Revista Educação, Artes e Inclusão, 2021)
A growing number of diagnostic data for children with autismo and, consequently, the number of calls to these people. Whereas there are several professionals who accompany them, we decided to investigate how the organization of these teams is. With this as a starting point, we list the following objectives: to analyze the organizational profile of the visits of groups on the participation of professionals; identify the presence of the joint Science used by the group and know the opinion of the professional as to what would be an efficient and effective group for the treatment of patients with autism. Based on this assumption, we ask: autistic children therapy groups use that kind of articulation between the sciences that make them? We conducted a field survey, descriptive quantitative/qualitative of nature. Two professionals working in 22 weekly visits to special children with autism were part of our research; of these, 7 were organized into groups of professionals, with a team characteristic described by the participants in the questionnaire. The result points to the organization of groups of the transdisciplinary type,without the professionals, in fact, have made this option.